Comparative estimation of surgical treatment methods of occlusive hydrocephaly - Kariev, G. M.; Tukhtaev, N. Kh.; Khalikov, N. Kh. (Ukrainian Neurosurgical Journal, 2009)
The retrospective analysis of surgical methods for occlusive hydrocephaly (OH) treatment at 121 patients was carried out. On the basis of the treatment efficiency analysis taking into consideration patient’s age, level and factors of occlusion and disease phase the algorithm for method choice for OH surgical treatment was proposed that allowed to decrease frequency of postoperative complications from 31,94 to 22,45%, of repeated operations — from 30,56 to 16,32% and lethality from 12,5 to 6,12%.